2013
DOI: 10.3171/2013.8.jns13844
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized double-blind crossover trial comparing subthalamic and pallidal deep brain stimulation for dystonia

Abstract: Object The authors' aim was to compare the subthalamic nucleus (STN) with the globus pallidus internus (GPi) as a stimulation target for deep brain stimulation (DBS) for medically refractory dystonia. Methods In a prospective double-blind crossover study, electrodes were bilaterally implanted in the STN and GPi of 12 patients with focal, multifocal, or generalized dystonia. Each patient was randomly selected to undergo initial bilateral stimulation of either the STN or the GPi for 6 months, followed by bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
63
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 40 publications
4
63
0
2
Order By: Relevance
“…For example, the Vim nucleus of the thalamus has been reported to be effective for patients with dystonic tremor, although in small numbers (~30 cases) [82]. The subthalamic nucleus (STN) has been studied as an alternative target for primary and tardive dystonia [83][84][85][86]. Most of these studies have included small numbers of patients, that is, fewer than 10 patients.…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…For example, the Vim nucleus of the thalamus has been reported to be effective for patients with dystonic tremor, although in small numbers (~30 cases) [82]. The subthalamic nucleus (STN) has been studied as an alternative target for primary and tardive dystonia [83][84][85][86]. Most of these studies have included small numbers of patients, that is, fewer than 10 patients.…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…A third rationale for adding GPi DBS in our patient was the prominence of dystonia among his symptoms. Clinical observation has suggested that pallidal stimulation may be beneficial for dystonic symptoms, 28 although subthalamic stimulation has recently been shown to also be effective for primary generalized and segmental dystonia. 22,28 Prior reports have studied the possibility of co-targeting STN and GPi in patients with PD.…”
mentioning
confidence: 99%
“…Other treatments have been studied for dystonia. Subthalamic nucleus stimulation and simultaneous GPi and subthalamic nucleus stimulation are emerging as promising in the surgical treatment of dystonia 105 . Apparently subthalamic nucleus stimulation does not impair working memory and attention, as has been reported in PD 106 .…”
mentioning
confidence: 99%